1973
DOI: 10.1161/01.cir.47.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ventricular Premature Contractions on Routine Electrocardiography and Subsequent Sudden Death from Coronary Heart Disease

Abstract: The association between ventricular premature contractions (VPC) on routine ECG and sudden death (SD) from coronary heart disease (CHD) during an ll-year period was examined in a historic prospective study of 1,214 white male factory workers, ages 35-69, in Canton, North Carolina. Prevalence of VPC was 92 (6.7%) increasing from 2% to 15% with age. Sixty of the 118 deaths were ascribed to CHD, 38 (63.3%) with 24-hour SD, and 27 (45%) with 1-hour SD. The relative risk of 1-hour SD for those with VPC was not incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Although much attention has been given to the problem of prehospital SCD,'"-' [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] several important areas remain poorly defined. These include: (1) conjectural, and information concerning rhythms which precede those monitored by rescue workers is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Although much attention has been given to the problem of prehospital SCD,'"-' [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] several important areas remain poorly defined. These include: (1) conjectural, and information concerning rhythms which precede those monitored by rescue workers is not available.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of acute myocardial infarction was based on clini cal (typical chest pain lasting >30 min), electrocardiographic (new Several studies have shown increased mortality associ ated with ventricular ectopic activity in survivors from acute myocardial infarction [1][2][3][4][5][6][7], In some previous stud ies, follow-up was relatively short, patient groups were rel atively small and arrhythmias were detected on standard electrocardiograms only. This report focuses on the 10-year prognostic significance of ventricular ectopic activity in a large cohort of patients (n = 1,737) after myocardial infarction who underwent 24-hour Holter monitoring be tween 7 and 21 (mean 12) days after the acute event.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…But, PVCs may still have an important role in risk stratification even if treatment with antiarrhythmic medications is not appropriate. A higher prevalence of PVCs has been seen in patients with coronary artery disease (Bikkina, Larson, & Levy, 1992), hypertension (Vogt et al, 1990), accompanying ECG abnormalities (Fisher & Tyroler, 1973), and nearly every form of structural heart disease. PVCs also increase with age (Flegg, 1988;Kostis et al, 1982).…”
Section: Pvcsmentioning
confidence: 99%
“…The 4% prevalence of PVCs found in our study compares favorably with a rate of 2-7% in previous epidemiologic studies including those using 2-min rhythm strips. (Crow et al, 1975;Fisher & Tyroler, 1973;Kostis et al, 1987;Simpson et al, 200). Overall, this is a retrospective analysis and, as such, should be considered hypothesis generating rather than conclusive evidence of a cause and effect relationship.…”
Section: Study Limitationsmentioning
confidence: 99%